HP0012 The discriminatory validity of the new zealand score for hip and knee surgery in a uk population. (1st June 2001) - Toye, FM; Lamb, SE; Barlow, JH; Wright, CC
Abstract : Background: There is currently no standardised method for prioritising patients joint replacement surgery in the UK. The New Zealand (NZ) score could be used to assist prioritisation. 1 This approach has not been tested in the UK. Objectives: To determine whether the NZ score is associated with measures of pain and function, in a sample of 176 people who were currently waiting for, or being considered for total knee replacement. Methods: Patients completed the WOMAC scores, a Likert scale for distress (0–4), and a 100 mm VAS for pain. Leg power was tested using a leg extensor power rig. The number of sit to stands in one minute was recorded. In NZ a cut off point of between 55–65 is used. Those scoring below 55 are not recommended for surgery. Patients were stratified into 2 groups. The first group included all those scoring below 55, and the second group all those who scored 55 or above. Spearman's correlation was performed to identify correlation between the NZ score and other measures. Mann-Whitney tests were performed in order to test differences between groups. Results: 44% were male, with a mean age of 69(SD9). Mean duration of symptoms was 10 years (SD12), and mean VAS score for pain was 57 (SD24). 68% were already listed for surgery. Significant correlations were found between the NZ score and all other measures p < 0.01 (2-tailed). A higher NZ score was associated with more pain, less functional ability and reduced strength. The Rho values are shown in the table. Median scores for all measurements were significantly different between the two groups p < 0.01 (2-tailed). 28% scored 55 or above, 85% of these were already listed for surgery, 67% were listed as "routine" cases and 33% were listed as "soon". Those scoring above 55 were weaker, had reduced function, and more pain than those scoring below 55. These differences were statistically and clinically significant. Conclusion: The NZ score is associated with pain and function in a UK population of patients waiting for, or being considered for total knee replacement surgery. Further research is needed to identify whether a score of 55 is the optimal cut off point. This cut off point did not distinguish between patients who were already listed for surgery and those who were not. However, it did identify higher patient need. Reference: Hadorn DC, Holmes AC. The New Zealand priority criteria project part1: overview. Br Med J. 1997;314:131–4